2001
DOI: 10.1002/bit.10120
|View full text |Cite
|
Sign up to set email alerts
|

Affinity purification of fibrinogen using a ligand from a peptide library

Abstract: An affinity resin containing the peptide ligand Phe-Leu-Leu-Val-Pro-Leu (FLLVPL) has been developed for the purification of fibrinogen. The ligand was identified by screening a solid-phase combinatorial peptide library using an immunostaining technique. The specific binding of fibrinogen to the ligand has been characterized by isothermal calorimetry and adsorption isotherms and is dominated by both hydrophobic interactions and ionic interactions with the N-terminal free amino group. The effective association c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 22 publications
(23 reference statements)
1
43
0
Order By: Relevance
“…In spite of this "small" volume of beads the experimental data have always been observed to be reproducible. To counterbalance this assessment, it has been several times demonstrated that a given protein can easily be captured by various peptide structures (Huang et al, 1996;Kaufman et al, 2002) and also that a single peptide structure (single bead) can easily capture various species .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this "small" volume of beads the experimental data have always been observed to be reproducible. To counterbalance this assessment, it has been several times demonstrated that a given protein can easily be captured by various peptide structures (Huang et al, 1996;Kaufman et al, 2002) and also that a single peptide structure (single bead) can easily capture various species .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was described when elucidating the influence of peptide length on protein capture , on one hand, and more recently when reporting protein patterns when the interaction was performed at different pHs ), on the other hand. Similar peptide libraries were described also as a source of affinity ligands for protein purification with impressive results for a number of proteins (Bastek et al, 2000;Kaufman et al, 2002;Yang et al, 2005). For a given protein more than one single peptide was systematically identified with different adsorption-desorption properties.…”
Section: Citationmentioning
confidence: 99%
“…Support Reference ((Arg-Thr-Tyr)4-Lys2-Lys-Gly IgG Sepharose (Fassina et al 2001) Asp-Ala-Ala-Gly IgG Agarose (Lund et al 2012) His-Trp-Arg-Gly-TrpVal IgG Toyopearl amino-650M resin (Menegatti et al 2012) His-Trp-Arg-Gly-TrpVal * Human IgG Toyopearl amino-650M resin (Yang et al 2009 Phe-Leu-Leu-Val-ProLeu Fibrinogen Toyopearl amino-650M resin (Kaufman et al 2002) (Gly-Ala-Met-His-LeuPro-Trp-His-Met-GlyThr-Leu)4…”
Section: Peptide Sequencementioning
confidence: 99%
“…Affinity peptides can be thought of as intermediate between these two cases, as they offer the potential for enormous diversity in chemical properties, and hence selectivity. Further, by using combinatorial methods based on either biological or chemical systems to generate large libraries of unique peptides (Buettner et al, 1996;Kaufman et al, 2002;Ladner, 1995;Sato et al, 2002), sequences may be identified with moderate binding affinities that are sufficient to capture the product without undue losses, but which are still capable of eluting the bound protein under mild conditions.…”
Section: Introductionmentioning
confidence: 99%